MANAJEMEN ASSET DAN INVENTARISASI ASSET DALAM RANGKA MEWUJUDKAN GOOD SCHOOL GOVERNANCE - Nuha, Sukma Uli; Hariyono, Anwar; Suwandi, Suwandi; Hidayati, Roziana Ainul (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
Community service activities aim to provide understanding and skills for the Muhammadiyah School Treasurer in Gresik Regency regarding school management and inventory processes. Community Service begins by giving a pre-test to participants so that the presenter can find out to what extent the material or materials to be taught have been mastered by participants regarding asset management. The next stage is counseling about asset management, asset depreciation and asset inventory. The next stage, participants were asked to summarize the asset data in their respective schools to Ms. Excel that has been prepared by the speaker. The next stage is a discussion regarding asset management and calculating the depreciation of assets owned by the school. The final stage is the final evaluation / post-test which is used to determine participants' understanding of the material that has been provided. The results of the training showed an increase in participants' understanding of the importance of asset management and having asset inventory data in their respective schools. This activity provides positive value in terms of effectiveness and efficiency of asset management and inventory management. This activity can also help schools to minimize the occurrence of human error and maintain the security of asset data contained in the school.